BEYOND PIOUS CRITICAL AGENCY: WOMEN, INTERFAITH MARRIAGE AND RELIGIOUS CONVERSION IN ACEH - Muhammad Ansor; Yaser Amri (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
Most studies discussing about interfaith marriage and religious conversion are ignoring woman's autonomy in selecting spouse as well as choosing religion. This paper examines the agency of women who converted due to marriage based on the experiences of four women in two areas in Aceh, the South East Aceh, and Aceh Singkil. Data was collected through observation and semi-structured interviews of four converted women, her husband, and her relatives. The phenomenon of religious conversion on the reason of marriage is placed in the feminist poststructuralist discourse, especially the concept of pious agency and critical piety agency. This paper challenges the view that says religious conversion on the reason of marriage will give the result to those who converted that religion to them is merely administrative matters and they lose their focus on building personal piety. Instead, this article argued the possibility of people who convert to other religion represent their religiosity after conversion as well as before conversion.